Ethics And Social Procedures In Lontara Pappaseng As A Guideline And Philosophy Of Life Of Buginese Society In South Sulawesi : (An Exploration of Buginese Philosophy in Expressions) - B, Soefarto; Nerawati, Ni Gusti Ayu Agung (Jayapangus Press, 2023)
Today's people seem to lost their direction and guidelines in life as a result from the demands of life which are getting heavier day by day so that a tendency for character emerges individualistic and less concerned about others. Apart from having six major religions, Indonesia is also very rich in values of local wisdom that is noble and very relevant to the sacred teachings of religion in life of the people of South Sulawesi, especially the Bugis people, have local wisdom in the form of literature works both in the form of speeches and Lontars. One of the works of Lontara literature which contains values ​​of Ethics and Decency is Lontara Pappaseng. Lontara Pappaseng contains many ethical and decency values we need to explore and develop so that it becomes a guideline for mankind, especially for the future of our young generation’s life in the society and the nation. In Lontara Pappaseng contains of advices in the form of human values, justice, courage, truth, honesty, loyalty, assertiveness and others that can be used as guidance and guidelines in everyday life in order to create a harmonious life both in household life, society and in the life of the nation and state. The research method used is a qualitative research approach with phenomenological method that is collecting data with participant observation to know the essential phenomena of participants in their life experiences because of this research focus on peeling study issues related to Ethical Values ​​(Tata Susila) contained in Lontara Pappaseng Toriolo and its meaning, in addition to this research as well using a qualitative approach with data collection techniques through literature study by tracing pappaseng lontara manuscripts and documentation studies. The data source used is the Lontara script in Buginese language with the Lontara script, however in this article the lontara script used is the manuscript that has been collected by the Buginese writer and humanist (translated into Indonesian). The existence of local wisdom values ​​in the form of Pappaseng is expected to be able to provide reinforcement of the functions of religion as a regulator of social obligation’s traffic through orders and prohibitions that are expected to materialize a peaceful social life.